Stone's Revenge: Deconstructing Hierarchy in ‘Cerita Batu’ - Lismalinda; Novita, Elmi; Rahardy, Iffah Fauziah; Arianto, Tomi (eScience Humanity Journal, 2024)
This paper analyzes the short story Cerita Batu through the lens of deconstruction, focusing on the reversal of hierarchical oppositions and the rejection of new hierarchical structures. The analysis identifies key binary oppositions in the text Man/Woman, Living Things/Inanimate Objects, and Happy/Sad and examines how these oppositions function within the narrative. The study highlights how the text initially presents dominant and marginal hierarchies, such as male dominance over female and human superiority over inanimate objects, which are later deconstructed. By reversing these hierarchies, the story reveals the interdependence between opposing elements: men and women, humans and stones, and happiness and sadness. The narrative demonstrates that these binary oppositions are not fixed, but fluid and interconnected, showing how meaning in the text is plural and resistant to singular interpretations. Ultimately, Cerita Batu emphasize the idea that oppositions are mutually constitutive, challenging conventional notions of dominance and subordination.